Pemberdayaan Masyarakat dalam Meningkatkan Kemandirian Kelompok Tani (Studi Kasus Kelompok Tani Indah Sakato Jorong Kasai Kenagarian Kasang Kecamatan Batang Anai ) - SARI DUSNI (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2018)
This article is titled Community Empowerment in Increasing the Independence of Farmers' Groups (A Case Study of Indah Sakato Farmers Group in Jorong Kasai Kenagarian Kasang in Batang Anai District). The method used is descriptive qualitative method. This article aims to describe and find out the form of the independence of the Indah Sakato Farmer Group at the Jorong Kasai Kenagarian Kasang in Batang Anai Subdistrict whether it is in accordance with the indicators of success in community empowerment. The results of the study illustrate that indicators of success in empowering farmer groups are still far from independence because there are still limited farmer groups to seek knowledge, because members generally go to elementary school so they cannot read, between members lack familiarity so empowerment is not smooth and seeks knowledge Organic fertilizer does not run smoothlyKey words: people empowerment, autonomy, farmer group.